Regional Economic Growth and Air Transportation in Indonesia especially outside Java: a Backward Method in Multiple Regression Model - Byna Kameswara; Tia Adelia Suryani (Diponegoro University, 2021)
In sustainable development, infrastructure has an important role, although infrastructure growth and investment have positive and negative impacts. Indonesia has a strategic program in the form of infrastructure improvement. However, due to the condition of Indonesia which is an archipelago, infrastructure development has only concentrated on Java, especially in Jakarta City. This resulted in a gap in infrastructure development outside of Java. This study identifies the relationship between infrastructure and the regional economy in Indonesia. Indonesia is an archipelagic country so that long-distance transportation, such as using airports, is an absolute necessity to support equitable economic activities and support sustainable development. The relationship between traffic on airports and regional economies is still debating and growing. Therefore, by looking at the characteristics of the archipelagic country, it is interesting to see the relationship between infrastructure and the regional economy in Indonesia. This research aims to provide an understanding of the effect of economic growth in airports and be able to be a stakeholder consideration to making policies about air transportation and regional economic growth evenly on island geography conditions such as Indonesia. The relationship between the two in this study is shown by looking at traffic in airports and 17 economic sectors of GRDP in six different regencies with similar characteristics. The model show the relationship in this study. This model built using a regression approach. The results of this model show the relationship between traffic in airports with regional economic sectors, especially outside the island of Java. The results of this study can be concluded that the effect is found between the economic sectors of the region on the existence of airports